Molecular study of carbapenem-resistant Pseudomonas aeruginosa causing wound infection in an Egyptian tertiary hospital - Nagwan Galal El Menofy; Mahmoud M Tawfick; Mona Shaban E M Badawy (Journal of Infection in Developing Countries, 2025)
Introduction: Pseudomonas aeruginosa is a bacterial pathogen that causes various acute and chronic human infections, including wound and burn infections, with serious consequences. This study aimed to determine the antimicrobial resistance profile of P. aeruginosa isolated from wound infections and investigate the molecular mechanism of carbapenem resistance.